Chromatin and Epigenetic Rearrangements in Embryonic Stem Cell Fate Transitions - Sun, Li; Fu, Xiuling; Ma, Gang; Hutchins, Andrew P. (Frontiers in Cell and Developmental Biology, 2021)
A major event in embryonic development is the rearrangement of the epigenetic information as the somatic genome is reprogrammed for a new round of organismal development. Epigenetic data is held in chemical modifications on DNA and histones, and there are dramatic and dynamic changes in these marks during embryogenesis. However, the mechanisms behind this intricate process and how it is regulating and responding to embryonic development remains unclear. As embryos develop from totipotency to pluripotency, they pass through several distinct stages that can be captured permanently or transiently in vitro. Pluripotent naïve cells resemble the early epiblast, and primed cells resemble the late epiblast, and blastomere-like cells have been isolated, although fully totipotent cells remain elusive. Experiments using these in vitro model systems have led to insights into chromatin changes in embryonic development, that has informed exploration of pre-implantation embryos. Intriguingly, human and mouse cells rely on different signaling and epigenetic pathways, and it remains a mystery why this variation exists. In this review, we will summarize the chromatin rearrangements in early embryonic development, drawing from genomic data from in vitro cell lines, and human and mice embryos.